Biobehavioral and psychosocial stress changes during three 8–12 month spaceflight analog missions with Mars-like conditions of isolation and confinement - Dunn Rosenberg, Jocelyn; Jannasch, Amber; Binsted, Kim; Landry, Steven (Frontiers in Physiology, 2022)
Prior theories about individual and team adaptation to living and working in an isolated and confined environment (ICE) have been derived from the experiences of individuals who winter-over in Antarctica or deploy for long durations in submarines. These theories are typically described as a 3- to 4-stage process with phases of excitement and elevated alertness, then followed by difficult phases, including depression and volatility. To further evaluate the applicability of these theories to long-duration human spaceflight missions, longitudinal stress responses to prolonged isolation and confinement of three 6-person crews during 8-12 month simulated Mars missions were characterized through metabolite profiling (biomarkers in hair and urine samples), wearables monitoring (sleep and activity levels), and self-reported ratings of stress, mood, social participation, and perceived health. These data were normalized, aggregated, and clustered to analyze longitudinal trends in biobehavioral and psychosocial stress measures. As a result, this analysis presents a theoretical model that triangulates aspects of prior theories with new evidence to describe ICE stress at HI-SEAS as 1) eustress of initial adaptation (high stress hormone levels at mission start), 2) deprivation due to prolonged isolation and confinement (decreasing dopamine and serotonin levels), 3) disruption of individual and team dynamics (changes in activity levels, mood, perceived stress, and social participation) and 4) asynchronous coping (changes in sleep-wake cycles, outlook, and team cohesion). These findings support several aspects of prior theories in combination, such as the elevated alertness at mission start and that adverse conditions are most likely to develop after the halfway point of a mission (e.g. for HI-SEAS 8-12 month missions, after approximately 6 months) followed by a period of volatility until the end (e.g. as stated in Rohrer’s theory, ups and downs until the end, not a renewed outlook at the end as described in 3rd quarter phenomenon theory).